Family Language Policy: the Maintenance of Latvian as a Heritage Language in the Diaspora - Martena, Sanita (Vilnius University Open Series, 2023)
This article explores the concept of family language policy in relation to child agency and parents’ discourse strategies in the context of the Latvian diaspora. Research is based on four interviews with parents from three countries: the United Kingdom, Norway and Greece. Respondents were recruited through Saturday/Sunday schools in the diaspora, addressing Latvian speakers who work there or whose children attend these schools. Both parents of all four families analysed in this study use Latvian at home. Data were collected using the Zoom platform during spring 2023 and are part of a larger study about family language policies in the diaspora. Currently, data are also gathered using methods such as audio recordings of interactions between parents and children and online classroom observations in Latvian (Saturday) schools. The main research questions for this article are: which language ideologies underlie language practices (language choices) at home involving parents and children, and which parental discourse strategies are used in families with regard to the multilingual language practices of their children.
Keywords: diaspora; family language policy; parental discourse strategies; language maintenance; Latvian